Politeness Strategies and Gender Interaction in The Great Gatsby: A Sociolinguistic Analysis - Benedicta Vania; Sumardiono; Imroatul Ma'fiyah (International Journal of English and Applied Linguistics (IJEAL), 2026)
This study explored the use of politeness strategies in gender interaction between Jay Gatsby and Daisy Buchanan in The Great Gatsby. It examined the types of politeness strategies employed by both characters, investigated the social factors that influenced their linguistic choices, and interpreted how those choices represented gendered interaction within the novel. A qualitative descriptive approach was adopted, with 73 utterances drawn from the characters' spoken dialogues serving as the research data. The data were collected through document analysis and examined using an interactive process of data reduction, data display, and conclusion drawing. The credibility of the findings was strengthened through theoretical triangulation. The sociolinguistic analysis revealed the presence of four politeness strategies in the interactions. Positive politeness appeared most frequently, accounting for 34.25% of the data, followed by negative politeness (28.77%), bald-on-record (20.55%), and off-record strategies (16.44%). Their use was influenced by relative power, social distance, and the rank of imposition in each conversational context. Gatsby tended to express solidarity and emotional closeness through positive politeness, while Daisy more often relied on indirect forms of communication that reflected caution and interpersonal distance. These findings indicated that politeness strategies functioned as meaningful linguistic resources for expressing social relationships and negotiating gender interaction, which reflected the social values portrayed in the novel.